The automated Greulich and Pyle: a coming-of-age for segmental methods? - Chapke, Rashmi; Mondkar, Shruti; Oza, Chirantap; Khadilkar, Vaman; Aeppli, Tim R. J.; Sävendahl, Lars; Kajale, Neha; Ladkat, Dipali; Khadilkar, Anuradha; Goel, Pranay (Frontiers in Artificial Intelligence, 2024)
The well-known Greulich and Pyle (GP) method of bone age assessment (BAA) relies on comparing a hand X-ray against templates of discrete maturity classes collected in an atlas. Automated methods have recently shown great success with BAA, especially using deep learning. In this Perspective we first review the success and limitations of various automated BAA methods. We then offer a novel hypothesis: When networks predict bone age that is not aligned with a GP reference class, it is not simply statistical error (although there is that as well); they are picking up nuances in the hand X-ray that lie 'outside that class'. In other words, trained networks predict distributions around classes. This raises a natural question: How can we further understand the reasons for a prediction to deviate from the nominal class age? We claim that segmental aging, that is, ratings based on characteristic bone groups can be used to qualify predictions. This so-called segmental GP method has excellent properties: It can not only help identify differential maturity in the hand but also provide a systematic way to extend the use of the current GP atlas to various other populations.